(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study examines the impact of COVID19 on Arab Financial markets performance measured by daily closing prices. The data was gathered from various formal sources such as over the period 1/43/2020 to 9/3/2021. The results showrd significantly positive impact of number of confirmef cases on market performance of Saudi Arabia, United Arab of Emirates and Egypt where as the impact is less significant for Oman and Jordan.